A Revised Efficiency Principle for the Taxation of Couples - Henrik Jacobsen Kleven; Klaus Thustrup Kreiner (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
We reconsider the result that efficient taxation involves a lower marginal tax on secondary earners than on primary earners. Introducing labor force participation responses into the analysis, we show that a second-earner tax allowance is better than selective marginal tax rates.
Keywords: H21; J22; D10; 330; optimal taxation; married couples; labor supply behavior; Familienbesteuerung; Wirtschaftliche Effizienz